Effect of Dietary Protein Levels and Soybean Oil Supplementation on Broiler Performance - Tabeidian, A.; Sadeghi, GH.; Pourreza, J. (International Journal of Poultry Science, 2005)
This study was conducted to examine the effect of different protein and soybean oil levels on broiler chickens. A total of 480 one-day old broiler chicks of a commercial breed (Ross 308) from both sex with equal ratio were placed in 32 pens, fifteen in each pen. Treatments were included soybean oil at 0, 2.5, 5 and 7.5% levels and crude protein levels were NRC (1994) recommendation and 10 percent more than NRC recommendation (NRC x 1.10). Each treatment replicated four times. Inclusion of soybean oil in diet had no significant effect on feed intake in chicks in NRC protein level. Feeding high protein diet resulted to more feed intake than NRC. Increasing diet protein up to 10 % more than NRC recommendation could not improve body weight gain in broiler chickens except for 7-21d old chicks that fed a diet containing no soybean oil and high protein level that resulted to highest weight gain. In 7-21 d old chicks feeding a diet with 2.5% soybean oil and a protein level 10% more than NRC recommendation resulted to lowest feed conversion ratio. Feeding different levels of soybean oil and protein had no effect of carcass, pancreas, intestine and preventriculus weight. Lowest abdominal fat was observed in chicks fed with a diet containing 7.5% soybean oil with NRC recommendation protein level. In chickens that fed with higher protein level, fat supplementation resulted to an increase in plasma triglyceride.